IMR 664: Electronic Record Keeping. Group assignment: Gundam Malaysia / Mohd Aqil Afnan Derahman and Muhammad Fawwaz Fida iy Mohd Fauzi - Derahman, Mohd Aqil Afnan; Mohd Fauzi, Muhammad Fawwaz Fida iy (2017)
Founder of Gundam.my - It all started out during the year 2010, We realised that there weren't really any Gundam Model Kits that was sold in Malaysia Market. Even in Hobby Shops, there were not many selection of Gundam Model Kits. Knowing that Gundam was such a famous and Iconic Anime, we are sure there is a lot of people or fans from Malaysia who are interested in collecting Gundam Model Kits but the issue was it was hard to get our hands on it especially for those who were from rural areas.